Infliximab in active early rheumatoid arthritis. Issue 2 (13th January 2004) - Breedveld, F C; Emery, P; Keystone, E; Patel, K; Furst, D E; Kalden, J R; St Clair, E W; Weisman, M; Smolen, J; Lipsky, P E; Maini, R N
Abstract : Objective: To examine the impact of the combination of infliximab plus methotrexate (MTX) on the progression of structural damage in patients with early rheumatoid arthritis (RA). Methods: Subanalyses were carried out on data for patients with early RA in the A nti-T NF T herapy in RA with C oncomitant T herapy (ATTRACT) study, in which 428 patients with active RA despite MTX therapy received placebo with MTX (MTX-only) or infliximab 3 mg/kg or 10 mg/kg every (q) 4 or 8 weeks with MTX (infliximab plus MTX) for 102 weeks. Early RA was defined as disease duration of 3 years or less; 82 of the 428 patients (19%) met this definition. Structural damage was assessed with the modified van der Heijde-Sharp score. The changes from baseline to week 102 in total modified van der Heijde-Sharp score were compared between the infliximab plus MTX groups and the MTX-only group. Results: The erosion and joint space narrowing scores from baseline to week 102 in the cohort of patients with early RA decreased significantly in each infliximab dose regimen compared with the MTX-only regimen. Consistent benefit was seen in the joints of both hands and feet. Conclusions: Infliximab combined with MTX inhibited the progression of structural damage in patients with early RA during the 2 year period of treatment. Early intervention with infliximab in patients with active RA despite MTX therapy may provide long term benefits by preventing radiographic progression and preserving joint integrity.